Molybdenum Can Regulate the Expression of Molybdase Genes, Affect Molybdase Activity and Metabolites, and Promote the Cell Wall Bio-Synthesis of Tobacco Leaves - Yuan Zhao; Yu Zhang; Kai Zhang; Jiashu Tian; Huanyu Teng; Zicheng Xu; Jiayang Xu; Huifang Shao; Wei Jia (Biology)
Molybdenum (Mo) is widely used as a micronutrient fertilizer to improve plant growth and soil quality. However, the interactions between cell wall biosynthesis and molybdenum have not been explored sufficiently. This study thoroughly investigated the regulatory effects of different concentrations of Mo on tobacco cell wall biosynthesis from physiological and metabolomic aspects. The results indicate that Mo treatment increased the Mo content of tobacco variety K326. Moreover, it significantly up-regulated the gene expression levels of molybdases (NR, AO, SO, XDH) and molybdate transporters in tobacco, whereby the gene expression levels of NR were upregulated by 28.48%, 52.51%, 173.05%, and 246.21%, respectively; and MOT1 and MOT2 were upregulated by 21.49/8.67%, 66.05/30.44%, 93.05/93.26%, and 166.11/114.29%, respectively. Additionally, Mo treatment regulated the synthesis of related enzymes, effectively promoted plant growth, and significantly increased biomass and dry matter accumulation, with the biomass in the leaves increasing significantly by 30.73%, 40.72%, 46.34%, and 12.88%, respectively. The FT-NIR spectroscopy results indicate that after Mo was applied to the soil, the quantity of C-O-C, -COOH, C-H, and N-H functional groups increased. Concurrently, the contents of cellulose, hemicellulose, lignin, protopectin, and soluble pectin in the leaves significantly increased, wherein the content of soluble pectin and hemicellulose increased significantly by 31.01/288.82%, 40.69/343.43%, 69.93/241.73%, and 196.88/223.26%, respectively. Furthermore, the cell walls thickened, increasing the ability of the plant to withstand disturbances. The metabolic network diagrams indicate that Mo regulated galactose metabolism, and arginine and proline acid biosynthesis. The contents of carbohydrates, spermidine, proline, quinic acid, IAA, flavonoids, and other substances were increased, increasing the levels of polysaccharides and pectin within the cell wall, controlling lignin production, and successfully enhancing resistance to abiotic stress. These results offer important perspectives for further investigations into the role of trace elements.